THE FUNDAMENTAL ROLE OF DEMOCRATIC MANAGEMENT AND COORDINATION IN PUBLIC EDUCATION NETWORK SCHOOLS - Maria da Silva, Josina; Berto Silva, Gledson; Edjanir Cândido Pereira, Maria; Margarete do Nascimento Mendonça, Maria; Holond de Lima Rocha, Kleyton; Maria Monteiro da Silva, Gilvana; José Melo dos Santos, Mozart; Carlos Vanderlei da Silva, José; da Silva Lima, Almir; Cristina Sousa, Maryone (Revista Gênero e Interdisciplinaridade, 2024)
This study analyzes the importance of democratic management and coordination in public schools, focusing on the emergence and evolution of this concept throughout history, as well as the different ways in which these principles operate, considering the diversity of profiles existing in each educational institution. The relevance of responsible bodies, such as the Department of Education, in monitoring compliance with these principles is highlighted. The study also addresses the steps that led to the adoption of democratic management as a way to improve educational policies, highlighting the presence of trained professionals to guarantee students’ educational rights. It is concluded that democratic management is essential to ensure students’ rights and fulfill the school’s fundamental role in the educational process.